GPS detection of ionospheric perturbation before the 13 February 2001, El Salvador earthquake - V. V. Plotkin (Natural Hazards and Earth System Sciences, 2003)
A large earthquake of M6.6 occurred on 13 February 2001 at 14:22:05 UT in El Salvador. We detected ionospheric perturbation before this earthquake using GPS data received from CORS network. Systematic decreases of ionospheric total electron content during two days before the earthquake onset were observed at set of stations near the earthquake location and probably in region of about 1000 km from epicenter. This result is consistent with that of investigators, which studied these phenomena with several observational techniques. However it is possible, that such TEC changes are simultaneously accompanied by changes due to solar wind parameters and Kp -index.